2019
DOI: 10.1152/japplphysiol.00897.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volume status on the estimation of mean systemic filling pressure

Abstract: 21Various methods for indirect assessment of mean systemic filling pressure (MSFP) 22 produce controversial results as compared to MSFP at zero blood flow. We recently 23 reported that the difference between MSFP at zero flow, measured by right atrial 24 balloon occlusion (MSFPRAO) and MSFP estimated using inspiratory holds depends 25 on the volume status. We now compare three indirect estimates of MSFP with 26 MSFPRAO in Euvolemia, Bleeding, and Hypervolemia, in a model of anesthetized pigs 27 (n=9) with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…This wide variation in MSFP values extends even further when alternative measurement techniques-right atrium occlusion (20), arm occlusion (33,34), a model analogue (30,(35)(36)(37) or cardiac arrest (38)-are considered. Comparing these measurement techniques revealed that they are not interchangeable (20,35), and their accuracy depends on the underlying volume state (39). In this experiment we indeed showed a significant influence of volume status on the MSFP_IH, without finding a cut-off value to discriminate euvolemia from hypervolemia.…”
mentioning
confidence: 66%
“…This wide variation in MSFP values extends even further when alternative measurement techniques-right atrium occlusion (20), arm occlusion (33,34), a model analogue (30,(35)(36)(37) or cardiac arrest (38)-are considered. Comparing these measurement techniques revealed that they are not interchangeable (20,35), and their accuracy depends on the underlying volume state (39). In this experiment we indeed showed a significant influence of volume status on the MSFP_IH, without finding a cut-off value to discriminate euvolemia from hypervolemia.…”
mentioning
confidence: 66%
“…Right ventricular afterload increases may therefore be a reason for left-sided stroke volume variation, even though averaged right and left stroke volumes must equal each other [8]. Measurements upstream of the lung may not be exposed to these issues, since the right heart directly handles venous return and therefore changes in volume state [19,20,34]. Stroke volume variation may then be of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was an independent, post hoc sub-study of an experiment on respiratory maneuvers and venous return. Baseline characteristics have been published before [19,20]. The study was conducted in accordance with the Guide for the Care and Use of Laboratory Animals (National Academy of Sciences, 1996) and Swiss National Guidelines and was approved by the Commission of Animal Experimentation of Canton Bern, Switzerland (approval BE 71/14), and this manuscript adheres to the applicable ARRIVE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Mean systemic filling pressures have been previously measured in intact rats [ 14 ], dogs [ 15 ] and pigs [ 16 ], producing values between 7 and 13 mmHg. MSFP has been measured in humans following cardiac arrest in intensive care [ 17 ] and estimated in various cohorts of patients in clinical settings [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%